Micro-nano particle / polymer composite building heat preservation and sound insulation material and preparation method thereof

By combining modified nanographite particles, modified nanosilica particles, aqueous polyurethane and auxiliary materials, high viscosity and high hardness micro-nanoparticle/polymer composite materials are prepared, and the hardness and viscosity of wall panels in the prior art are solved. The poor problem achieves better structural stability and thermal insulation effect.

CN119192822APending Publication Date: 2024-12-27SICHUAN DAFENG LUSEN ENERGY SAVING NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411478029.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

While improving the thermal insulation performance of buildings, existing polymer microsphere insulation dry powder coatings have poor hardness and viscosity, which cannot effectively improve the service life and structural stability of wall panels.

Method used

Modified nanographite particles, modified nanosilicon dioxide particles and aqueous polyurethane are mixed with glass fiber powder, alumina powder, microporous calcium silicate powder and other auxiliary materials according to specific mass ratios, and micro-nanometers are prepared by sonication and emulsification and dispersion technology. Particle/polymer composite material forms high viscosity and high hardness thermal insulation coatings.

Benefits of technology

It significantly improves the structural stability, stain resistance and bonding strength of the wall panel, extends the service life, and enhances the thermal insulation and sound insulation effects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and discloses a micro-nano particle / polymer composite building heat preservation and sound insulation material which is prepared from modified nano graphite particles, modified nano silicon dioxide particles, waterborne polyurethane and an auxiliary additive, and the auxiliary additive is composed of glass fiber powder, aluminum oxide powder and microporous calcium silicate powder; the invention further discloses a preparation method of the micro-nano particle / polymer composite building heat preservation and sound insulation material. The preparation method comprises the following steps: S1, preparing the modified nano graphite particles; s2, preparing modified nano silicon dioxide particles; s3, preparation of waterborne polyurethane; and S4, preparing the composite material. The micro-nano particle / polymer composite building heat preservation and sound insulation material prepared by the invention can improve the structural stability of a wallboard; hard boards of the wallboards are added, and deformation of the wallboards is reduced; in addition, the bonding strength of the material and the wallboard is high, and the service life of the wallboard is prolonged; and the heat insulation and sound insulation effects of the wallboard can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a micro-nano particle / polymer composite building thermal insulation and sound insulation material and a preparation method thereof. Background Art

[0002] With the threat of energy crisis and climate change, building energy conservation has become a global focus; as an important part of a building, the thermal insulation performance of wall panels directly affects indoor temperature regulation and energy consumption; by arranging thermal insulation and sound insulation materials, the conduction and convection of indoor and outdoor temperatures can be effectively reduced, the thermal insulation performance of buildings can be improved, and the energy consumption of heating and cooling can be reduced; among them, thermal insulation and sound insulation coatings have the advantages of high efficiency sound insulation, environmental protection, convenient construction, and a wide range of applications, and therefore have been widely used.

[0003] A Chinese patent discloses a polymer microsphere thermal insulation dry powder coating (authorization announcement number CN101250343B). This patented technology has the common characteristics of thermal resistance and heat capacity materials, with outstanding weather resistance and particularly excellent stain resistance. The hollow fiber provides good thermal insulation performance, and also greatly improves the tensile, crack and flexural properties. Hollow glass or ceramic microspheres, hollow fibers and polymer microspheres are graded according to particle size to form a good barrier layer, which greatly improves the thermal insulation performance. The use of powder material supply greatly reduces transportation and storage costs, and is convenient for storage and construction, but its hardness and viscosity are not good, and it cannot effectively improve the service life of the wallboard. Summary of the invention

[0004] The object of the present invention is to provide a micro-nano particle / polymer composite building thermal insulation and sound insulation material and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The micro-nano particle / polymer composite building thermal insulation and sound insulation material is prepared from modified nano graphite particles, modified nano silicon dioxide particles, water-based polyurethane and auxiliary material additives in a mass ratio of (5-10): (5-10): (20-30): (10-15), wherein the auxiliary material additives are prepared from glass fiber powder, alumina powder and microporous calcium silicate powder in a mass ratio of (4-6): (3-5): (3-5).

[0007] As a further solution of the present invention: the particle size of the glass fiber powder is 10-50 um, the particle size of the alumina powder is 200-300 nm, and the particle size of the microporous calcium silicate powder is 100-300 nm.

[0008] The preparation method of the micro-nano particle / polymer composite building thermal insulation and sound insulation material comprises the following steps:

[0009] S1. Preparation of modified nano-graphite particles: 20-25 parts of graphite oxide powder are taken by mass, added to 10-12 parts of dimethylformamide solvent, and then 12-15 parts of toluene diisocyanate and 0.3-0.5 parts of dibutyltin dilaurate are added. After ultrasonic treatment, 10-12 parts of acetone are added, and after sufficient oscillation, the mixture is allowed to stand for 36-48 hours, and the lower layer of solution is taken; after drying, the mixture is ground into powder to obtain modified nano-graphite particles for standby use;

[0010] S2, preparation of modified nano-silica particles: 10-15 parts of nano-silica particles are taken by mass, added to 150-200 parts of toluene, and after ultrasonic treatment, 2-3 parts of terminal-NCO polyurethane prepolymer, 2-3 parts of rare earth aluminate coupling agent and 2-3 parts of silane coupling agent are added, and after mixing and stirring, the surface of the nano-silica particles is modified; after drying, the mixture is ground into powder to obtain modified nano-silica particles for standby use;

[0011] S3, preparation of waterborne polyurethane: take 25-30 parts of polypropylene glutarate by mass, preheat to 75-80° C. under nitrogen protection, add 25-30 parts of toluene diisocyanate, mix well, add 80-100 parts of dimethylol propionic acid, stir and mix, add 10-15 parts of butanediol and 30-35 parts of triethanolamine, stir, add 30-35 parts of ethylenediamine and 150-200 parts of deionized water, stir well, and obtain waterborne polyurethane emulsion for standby use;

[0012] S4. Preparation of composite materials: Take 5-10 parts of modified nano graphite particles and 5-10 parts of modified nano silicon dioxide particles by mass, add them into 20-30 parts of aqueous polyurethane emulsion, and continuously emulsify and disperse them, then add 10-15 parts of auxiliary material additives, emulsify and disperse them evenly, and the obtained emulsion is the micro-nano particle / polymer composite building thermal insulation and sound insulation material.

[0013] As a further solution of the present invention: in the step S1, the preparation method of graphite oxide is as follows:

[0014] S11, take 80-100 parts of carbon powder and 20-30 parts of sodium nitrate by mass, add them to 120-150 parts of concentrated sulfuric acid with a mass concentration of 70% to 80% in an ice water bath environment, stir continuously, add 30-40 parts of potassium permanganate, heat to 90°C at a rate of 0.5-0.8°C / min, and react for 0.5-1h;

[0015] S12, adding 800-1000 parts of hydrogen peroxide with a mass concentration of 8%-10%, stirring for reaction, filtering, washing, drying, and grinding into powder to obtain graphite oxide powder.

[0016] As a further solution of the present invention: in the step S2, the preparation method of nano silicon dioxide particles is:

[0017] 30-40 parts of ethyl orthosilicate, 15-25 parts of ammonia water with a mass concentration of 25%-30%, 10-20 parts of deionized water and 400-500 parts of ethanol are mixed, and stirred for hydrolysis at 35-40°C for 2-2.5 hours; after centrifugation, washing with water and drying, nano silicon dioxide particles are obtained.

[0018] As a further solution of the present invention: in the steps S1 and S2, the frequency of the ultrasonic treatment is 1-1.5 hkHZ, and the time is 1-1.5 h.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The invention is prepared from modified nano graphite particles, modified nano silicon dioxide particles, waterborne polyurethane and auxiliary material additives, wherein the auxiliary material additives are composed of glass fiber powder, aluminum oxide powder and microporous calcium silicate powder; the prepared micro-nano particle / polymer composite building thermal insulation and sound insulation material can improve the structural stability of the wallboard; increase the hardness of the wallboard and reduce its deformation; improve the stain resistance of the wallboard and ensure the cleanliness of its surface; and the material has high bonding strength with the wallboard, thereby increasing the service life of the wallboard; and can effectively improve the thermal insulation and sound insulation effects of the wallboard. DETAILED DESCRIPTION

[0021] Example 1

[0022] In an embodiment of the present invention, a micro-nano particle / polymer composite building thermal insulation and sound insulation material is prepared from modified nano graphite particles, modified nano silicon dioxide particles, water-based polyurethane and auxiliary material additives in a mass ratio of 1:1:4:2, wherein the auxiliary material additives are glass fiber powder with a particle size of 10um, alumina powder with a particle size of 200nm, and microporous calcium silicate powder with a particle size of 100nm, mixed in a mass ratio of 4:3:3.

[0023] The preparation method of the micro-nano particle / polymer composite building thermal insulation and sound insulation material comprises the following steps:

[0024] S1. Preparation of modified nanographite particles: Take 80 parts of carbon powder and 20 parts of sodium nitrate by mass, add them to 120 parts of concentrated sulfuric acid with a mass concentration of 70% in an ice-water bath environment, stir continuously, add 30 parts of potassium permanganate, heat to 90°C at a rate of 0.5°C / min, and react for 0.5h; then add 800 parts of hydrogen peroxide with a mass concentration of 8%, stir for reaction, filter, wash, dry, and grind into powder to obtain graphite oxide powder for standby use;

[0025] Then, 20 parts of graphite oxide powder are taken by mass, added to 10 parts of dimethylformamide solvent, and then 12 parts of toluene diisocyanate and 0.3 parts of dibutyltin dilaurate are added. After ultrasonic treatment at a frequency of 1 kHz for 1.5 hours, 10 parts of acetone are added, and after sufficient shaking, the mixture is allowed to stand for 36 to 48 hours, and the lower layer of solution is taken; after drying, the mixture is ground into powder to obtain modified nano-graphite particles for later use;

[0026] S2. Preparation of modified nano-silica particles: 30 parts of tetraethyl orthosilicate, 15 parts of 25% ammonia water, 10 parts of deionized water and 400 parts of ethanol were mixed, and stirred for hydrolysis at 35° C. for 2 h; centrifuged, washed with water, and dried to obtain nano-silica particles for later use;

[0027] Then, 10 parts of nano-silica particles are taken by mass, added to 150 parts of toluene, and ultrasonically treated at a frequency of 1 kHz for 1.5 hours, and then 2 parts of terminal-NCO polyurethane prepolymer, 2 parts of rare earth aluminate coupling agent and 2 parts of silane coupling agent are added, and after mixing and stirring, the surface of the nano-silica particles is modified; after drying, the particles are ground into powder to obtain modified nano-silica particles for later use;

[0028] S3, preparation of waterborne polyurethane: take 25 parts of polypropylene glutarate by mass, preheat to 75° C. under nitrogen protection, add 25 parts of toluene diisocyanate, mix well, add 80 parts of dimethylol propionic acid, stir and mix, add 10 parts of butanediol and 30 parts of triethanolamine, stir, add 30 parts of ethylenediamine and 150 parts of deionized water, stir well, and obtain waterborne polyurethane emulsion for standby use;

[0029] S4. Preparation of composite materials: Take 5 parts of modified nano graphite particles and 5 parts of modified nano silicon dioxide particles by mass, add them into 20 parts of aqueous polyurethane emulsion, and continuously emulsify and disperse them. Then add 4 parts of glass fiber powder with a particle size of 10um, 3 parts of alumina powder with a particle size of 200nm, and 3 parts of microporous calcium silicate powder with a particle size of 100nm. Emulsify and disperse them evenly. The obtained emulsion is the micro-nano particle / polymer composite building thermal insulation and sound insulation material.

[0030] Example 2

[0031] In an embodiment of the present invention, a micro-nano particle / polymer composite building thermal insulation and sound insulation material is prepared from modified nano graphite particles, modified nano silicon dioxide particles, water-based polyurethane and auxiliary material additives in a mass ratio of 8:8:25:12, wherein the auxiliary material additives are glass fiber powder with a particle size of 25um, alumina powder with a particle size of 250nm, and microporous calcium silicate powder with a particle size of 200nm, mixed in a mass ratio of 1:1:1.

[0032] The preparation method of the micro-nano particle / polymer composite building thermal insulation and sound insulation material comprises the following steps:

[0033] S1. Preparation of modified nanographite particles: 90 parts of carbon powder and 25 parts of sodium nitrate are taken by mass, added to 135 parts of concentrated sulfuric acid with a mass concentration of 75% in an ice-water bath environment, stirred continuously, and 35 parts of potassium permanganate are added, and the temperature is raised to 90°C at a rate of 0.65°C / min, and the reaction is carried out for 0.75h; then 900 parts of hydrogen peroxide with a mass concentration of 9% are added, stirred for reaction, filtered, washed, dried, and ground into powder to obtain graphite oxide powder for standby use;

[0034] Then, 22 parts of graphite oxide powder were taken by mass, added to 11 parts of dimethylformamide solvent, and then 13 parts of toluene diisocyanate and 0.4 parts of dibutyltin dilaurate were added. After ultrasonic treatment at a frequency of 1.2 kHz for 1.2 hours, 11 parts of acetone were added, and after sufficient shaking, the mixture was allowed to stand for 40 hours, and the lower layer of solution was taken; after drying, the mixture was ground into powder to obtain modified nano-graphite particles for later use;

[0035] S2. Preparation of modified nano-silica particles: 35 parts of tetraethyl orthosilicate, 20 parts of ammonia water with a mass concentration of 28%, 15 parts of deionized water and 450 parts of ethanol were mixed, and stirred for hydrolysis at 38° C. for 2.2 h; centrifuged, washed with water, and dried to obtain nano-silica particles for later use;

[0036] Then, 12 parts of nano-silica particles are taken by mass, added to 180 parts of toluene and stirred for 30 minutes, and then ultrasonically treated at a frequency of 1.2 kHz for 1.2 hours, and then 2.5 parts of terminal-NCO polyurethane prepolymer, 2.5 parts of rare earth aluminate coupling agent and 2.5 parts of silane coupling agent are added, and after mixing and stirring, the surface of the nano-silica particles is modified; after drying, the nano-silica particles are ground into powder to obtain modified nano-silica particles for standby use;

[0037] S3, preparation of waterborne polyurethane: take 28 parts of polypropylene glutarate by mass, preheat to 78° C. under nitrogen protection, add 28 parts of toluene diisocyanate, mix well, add 90 parts of dimethylol propionic acid, stir and mix, add 12 parts of butanediol and 32 parts of triethanolamine, stir, add 32 parts of ethylenediamine and 180 parts of deionized water, stir well, and obtain waterborne polyurethane emulsion for standby use;

[0038] S4. Preparation of composite materials: Take 8 parts of modified nano graphite particles and 8 parts of modified nano silicon dioxide particles by mass, add them into 25 parts of aqueous polyurethane emulsion, and continuously emulsify and disperse them. Then add 4 parts of glass fiber powder with a particle size of 25um, 4 parts of alumina powder with a particle size of 200nm, and 4 parts of microporous calcium silicate powder with a particle size of 250nm. Emulsify and disperse them evenly. The obtained emulsion is the micro-nano particle / polymer composite building thermal insulation and sound insulation material.

[0039] Example 3

[0040] In an embodiment of the present invention, a micro-nano particle / polymer composite building thermal insulation and sound insulation material is prepared from modified nano graphite particles, modified nano silicon dioxide particles, water-based polyurethane and auxiliary material additives in a mass ratio of 2:2:5:3, wherein the auxiliary material additives are glass fiber powder with a particle size of 50um, alumina powder with a particle size of 300nm, and microporous calcium silicate powder with a particle size of 300nm, mixed in a mass ratio of 6:5:4.

[0041] The preparation method of the micro-nano particle / polymer composite building thermal insulation and sound insulation material comprises the following steps:

[0042] S1. Preparation of modified nanographite particles: Take 100 parts of carbon powder and 30 parts of sodium nitrate by mass, add them to 150 parts of concentrated sulfuric acid with a mass concentration of 80% in an ice-water bath environment, stir continuously, add 40 parts of potassium permanganate, heat to 90°C at a rate of 0.8°C / min, and react for 0.5h; then add 1000 parts of hydrogen peroxide with a mass concentration of 10%, stir for reaction, filter, wash, dry, and grind into powder to obtain graphite oxide powder for standby use;

[0043] Then, 25 parts of graphite oxide powder were taken by mass, added to 12 parts of dimethylformamide solvent, and then 15 parts of toluene diisocyanate and 0.5 parts of dibutyltin dilaurate were added. After ultrasonic treatment at a frequency of 1.5 kHz for 1 hour, 12 parts of acetone were added, and after sufficient shaking, the mixture was allowed to stand for 48 hours, and the lower layer of solution was taken; after drying, the mixture was ground into powder to obtain modified nano-graphite particles for later use;

[0044] S2. Preparation of modified nano-silica particles: 40 parts of tetraethyl orthosilicate, 25 parts of ammonia water with a mass concentration of 30%, 20 parts of deionized water and 500 parts of ethanol were mixed, and stirred for hydrolysis at 40° C. for 2 h; centrifuged, washed with water, and dried to obtain nano-silica particles for later use;

[0045] Then, 15 parts of nano-silica particles are taken by mass, added to 200 parts of toluene, and ultrasonically treated at a frequency of 1.5 kHz for 1 hour, and then 3 parts of terminal-NCO polyurethane prepolymer, 3 parts of rare earth aluminate coupling agent and 3 parts of silane coupling agent are added, and after mixing and stirring, the surface of the nano-silica particles is modified; after drying, the mixture is ground into powder to obtain modified nano-silica particles for standby use;

[0046] S3, preparation of waterborne polyurethane: take 30 parts of polypropylene glutarate by mass, preheat to 80° C. under nitrogen protection, add 30 parts of toluene diisocyanate, mix well, add 100 parts of dimethylol propionic acid, stir and mix, add 15 parts of butanediol and 35 parts of triethanolamine, stir, add 35 parts of ethylenediamine and 200 parts of deionized water, stir well, and obtain waterborne polyurethane emulsion for standby use;

[0047] S4. Preparation of composite materials: Take 10 parts of modified nano graphite particles and 10 parts of modified nano silicon dioxide particles by mass, add them into 30 parts of aqueous polyurethane emulsion, and continuously emulsify and disperse them. Then add 6 parts of glass fiber powder with a particle size of 50um, 5 parts of alumina powder with a particle size of 300nm, and 4 parts of microporous calcium silicate powder with a particle size of 300nm. Emulsify and disperse them evenly. The obtained emulsion is the micro-nano particle / polymer composite building thermal insulation and sound insulation material.

[0048] In order to better illustrate the technical effects of the present invention, the following embodiments are described:

[0049] The wallboard prepared in the preparation method of the green prefabricated building wallboard disclosed in the comparative document 1 (CN104863305B) was selected as a sample, and the thickness of the sample was 5 cm; and the sample was used as a control group;

[0050] The emulsions prepared in Examples 1 to 3 of the present invention were respectively selected and coated on the sample plates to form coatings with a coating thickness of 2 mm, which were respectively referred to as Example 1 Group, Example 2 Group and Example 3 Group;

[0051] The coating prepared in Example 1 of a polymer microsphere thermal insulation dry powder coating disclosed in reference document 2 (CN101250343B) was applied on a sample to form a coating with a thickness of 2 mm as a comparative example group;

[0052] 1. The water absorption (unit: 100%), hardness (unit: MPa), stain resistance (reflectivity difference, unit: 100%) and viscosity (unit: MPa·s) of the coatings in Example 1, Example 2, Example 3 and the comparative example group were measured respectively; wherein, the sample was tilted 45° and placed outdoors for one month, and the reflectivity of the sample before and after the experiment was tested with a reflectivity meter, and the reflectivity difference was calculated; and recorded in the following Table 1.

[0053] 2. Measure the thermal conductivity (unit: W / (m·K)) and sound insulation coefficient (unit: dB) of the samples in Example 1, Example 2, Example 3 and the comparative example group respectively; record them in the following Table 1.

[0054] Water absorption hardness Reflectivity Difference Viscosity Thermal conductivity Sound insulation coefficient Control group / / / / 0.11 45.6 Example 1 Group 6.2% 0.81 2.75% 59.1 0.06 62.4 Example 2 Group 6.2% 0.77 2.74% 58.4 0.06 62.0 Example 3 Group 6.1% 0.77 2.69% 58.7 0.06 62.1 Comparative group 8.4% 0.62 3.87% 51.5 0.08 57.2

[0055] From Table 1 above, it can be concluded that the water absorption rate of the coating in Example 1, Example 2 and Example 3 is significantly lower than that in the comparative example group, and thus it can be concluded that the coating in Example 1, Example 2 and Example 3 can improve the thermal insulation performance of the sample and enhance its structural stability;

[0056] The hardness of the coating in Example 1, Example 2 and Example 3 is significantly greater than that in the comparative example group, so it is concluded that the coating in Example 1, Example 2 and Example 3 can increase the hardness of the sample and reduce its deformation;

[0057] The reflectivity difference of the coatings in Example 1, Example 2 and Example 3 is significantly smaller than that in the comparative example group, so it can be concluded that the coatings in Example 1, Example 2 and Example 3 can improve the anti-fouling performance of the sample and ensure the cleanliness of its surface;

[0058] The viscosity of the coating in Example 1, Example 2 and Example 3 is significantly greater than that in the comparative example group, so it can be concluded that the coating in Example 1, Example 2 and Example 3 can increase the bonding strength between the coating and the sample and improve its service life;

[0059] The thermal conductivity of the samples in Example 1, Example 2, Example 3 and the comparative example group is significantly lower than that in the control group; however, the thermal conductivity of the samples in Example 1, Example 2 and Example 3 is significantly lower than that in the comparative example group; thus, it is concluded that the coatings in Example 1, Example 2 and Example 3 have excellent thermal insulation effects;

[0060] The sound insulation coefficients of the samples in Example 1, Example 2, Example 3 and the comparative group are significantly greater than those in the control group; but the sound insulation coefficients of the samples in Example 1, Example 2 and Example 3 are significantly greater than those in the comparative group; thus, it can be concluded that the coatings in Example 1, Example 2 and Example 3 have excellent sound insulation effects.

[0061] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. Micro-nano particle / polymer composite building thermal insulation and sound insulation material, characterized in that: The invention is prepared from modified nano graphite particles, modified nano silicon dioxide particles, waterborne polyurethane and auxiliary material additives in a mass ratio of (5-10): (5-10): (20-30): (10-15), wherein the auxiliary material additives are prepared from glass fiber powder, alumina powder and microporous calcium silicate powder in a mass ratio of (4-6): (3-5): (3-5).

2. The micro-nano particle / polymer composite building thermal insulation and sound insulation material according to claim 1, characterized in that: The particle size of the glass fiber powder is 10-50 um, the particle size of the alumina powder is 200-300 nm, and the particle size of the microporous calcium silicate powder is 100-300 nm.

3. A method for preparing the micro-nano particle / polymer composite building thermal insulation and sound insulation material according to claim 1, characterized in that: The following steps are involved: S1. Preparation of modified nano-graphite particles: 20-25 parts of graphite oxide powder are taken by mass, added to 10-12 parts of dimethylformamide solvent, and then 12-15 parts of toluene diisocyanate and 0.3-0.5 parts of dibutyltin dilaurate are added. After ultrasonic treatment, 10-12 parts of acetone are added, and after sufficient oscillation, the mixture is allowed to stand for 36-48 hours, and the lower layer of solution is taken; after drying, the mixture is ground into powder to obtain modified nano-graphite particles for standby use; S2, preparation of modified nano-silica particles: 10-15 parts of nano-silica particles are taken by mass, added to 150-200 parts of toluene, and after ultrasonic treatment, 2-3 parts of terminal-NCO polyurethane prepolymer, 2-3 parts of rare earth aluminate coupling agent and 2-3 parts of silane coupling agent are added, and after mixing and stirring, the surface of the nano-silica particles is modified; after drying, the mixture is ground into powder to obtain modified nano-silica particles for standby use; S3, preparation of waterborne polyurethane: take 25-30 parts of polypropylene glutarate by mass, preheat to 75-80° C. under nitrogen protection, add 25-30 parts of toluene diisocyanate, mix well, add 80-100 parts of dimethylol propionic acid, stir and mix, add 10-15 parts of butanediol and 30-35 parts of triethanolamine, stir, add 30-35 parts of ethylenediamine and 150-200 parts of deionized water, stir well, and obtain waterborne polyurethane emulsion for standby use; S4. Preparation of composite materials: Take 5-10 parts of modified nano graphite particles and 5-10 parts of modified nano silicon dioxide particles by mass, add them into 20-30 parts of aqueous polyurethane emulsion, and continuously emulsify and disperse them, then add 10-15 parts of auxiliary material additives, emulsify and disperse them evenly, and the obtained emulsion is the micro-nano particle / polymer composite building thermal insulation and sound insulation material.

4. The method for preparing the micro-nano particle / polymer composite building thermal insulation and sound insulation material according to claim 3, characterized in that: In the step S1, the preparation method of graphite oxide is as follows: S11, take 80-100 parts of carbon powder and 20-30 parts of sodium nitrate by mass, add them to 120-150 parts of concentrated sulfuric acid with a mass concentration of 70%-80% in an ice water bath environment, stir continuously, add 30-40 parts of potassium permanganate, heat to 90°C at a rate of 0.5-0.8°C / min, and react for 0.5-1h; S12, adding 800-1000 parts of hydrogen peroxide with a mass concentration of 8%-10%, stirring for reaction, filtering, washing, drying, and grinding into powder to obtain graphite oxide powder.

5. The method for preparing the micro-nano particle / polymer composite building thermal insulation and sound insulation material according to claim 3, characterized in that: In the step S2, the preparation method of nano silicon dioxide particles is: 30-40 parts of ethyl orthosilicate, 15-25 parts of ammonia water with a mass concentration of 25%-30%, 10-20 parts of deionized water and 400-500 parts of ethanol are mixed, and then stirred and hydrolyzed at 35-40°C for 2-2.5 hours; after centrifugation, washing with water and drying, nano-silicon dioxide particles are obtained.

6. The method for preparing the micro-nano particle / polymer composite building thermal insulation and sound insulation material according to claim 3, characterized in that: In the steps S1 and S2, the frequency of the ultrasonic treatment is 1-1.5 hkHZ, and the time is 1-1.5 h.